Magnetic resonance imaging in the differential diagnosis of true placenta accreta: a clinical case - E. V. Tarachkova; L. A. Meshcheryakova; M. A. Shorikov; A. F. Maslennikov; V. O. Panov; V. V. Kuznetsov (ABV-press, 2016)
True placenta accreta is the attachment of chorionic villi to the myometrium, possibly penetrating into the thickness of the myometrium and its outside, including through the serous tunic. The main current diagnostic techniques are considered to be ultrasonography, laboratory diagnosis (elevated human chorionic gonadotropin and placental lactogen levels), and clinical data (pain and vaginal discharge). Magnetic resonance imaging is deemed to be an adjuvant technique. By using a clinical example, this paper considers the capabilities of magnetic resonance imaging to diagnose this abnormality and to choose a right treatment policy. The abnormality is compared with the conditions (trophoblastic tumor and myoma with lysis) that are similar in their diagnosis and magnetic resonance pattern). The disorder in question is rather rare and its detailed consideration, determination of the capabilities of various techniques, and comparison with externally similar cases areimportant for the development of diagnostic opportunities.